2015
DOI: 10.1002/jor.22841
|View full text |Cite
|
Sign up to set email alerts
|

A rabbit model demonstrates the influence of cartilage thickness on intra‐articular drug delivery and retention within cartilage

Abstract: For evaluation of new approaches to drug delivery into cartilage, the choice of an animal model is critically important. Since cartilage thickness varies with animal size, different levels of drug uptake, transport and retention should be expected. Simple intra-articular injection can require very high drug doses to achieve a concentration gradient high enough for drug diffusion into cartilage. New approaches involve nanoparticle delivery of functionalized drugs directly into cartilage; however, diffusion-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 30 publications
3
57
0
Order By: Relevance
“…Due to the unanticipated closure of this vendor during the study, the final ten rabbits were ordered from an alternate vendor, Covance Research Products (Denver, PA, USA). The thickness of rabbit tibial cartilage was measured to be between 350–550 μm (Bajpayee et al , 2015), consistent with previously reported data (Hoch et al , 1983). Generally, by 8 months of age, the growth plates in the distal femur and proximal tibia are closed, thereby defining skeletal maturity (Hunziker et al , 2007; Masoud et al , 1986).…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…Due to the unanticipated closure of this vendor during the study, the final ten rabbits were ordered from an alternate vendor, Covance Research Products (Denver, PA, USA). The thickness of rabbit tibial cartilage was measured to be between 350–550 μm (Bajpayee et al , 2015), consistent with previously reported data (Hoch et al , 1983). Generally, by 8 months of age, the growth plates in the distal femur and proximal tibia are closed, thereby defining skeletal maturity (Hunziker et al , 2007; Masoud et al , 1986).…”
Section: Methodssupporting
confidence: 89%
“…The residence time for avidin (and other solutes) in cartilage is proportional to the square of cartilage thickness (Bajpayee et al , 2015). Since cartilage thickness is related to joint size, the use of animals larger than mice or rats is important for generating intra-cartilage drug residence times that more closely approximate what would occur in humans.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We are bipeds as opposed to quadrupeds, our joint biomechanics and anatomy is distinct, including for example vast differences in the thickness of cartilage compared with species used in pre-clinical research, that likely has important implications for therapeutic development 12 . Similarly during evolution the human brain underwent extraordinary development, and along with that the arguably unique perception of self and complex cognitive capabilities and social interactions.…”
Section: The Argument For "Man"mentioning
confidence: 99%